2007
DOI: 10.1111/j.1479-828x.2007.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

The Vabra aspirator versus the Pipelle device for outpatient endometrial sampling

Abstract: This study proved that the Vabra aspirator was not as effective as the Pipelle device in obtaining endometrial tissue for histological diagnosis. Despite its higher price per unit, the Pipelle device was a more cost-effective tool for outpatient endometrial assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
1
21
0
1
Order By: Relevance
“…The Pipelle device has been shown, in the context of a randomized trial, to be superior to the Vabra aspirator (Berkeley Medevices Inc; Richmond, CA; USA), with adequate tissue being found in 73.3% vs 52.4% of cases 54 (Class 1b). The Pipelle device has also been compared with the Explora catheter (CooperSurgical Inc; Trumbull, CT; USA) in a randomized …”
Section: Comparison Of Office-based Sampling Systemsmentioning
confidence: 99%
“…The Pipelle device has been shown, in the context of a randomized trial, to be superior to the Vabra aspirator (Berkeley Medevices Inc; Richmond, CA; USA), with adequate tissue being found in 73.3% vs 52.4% of cases 54 (Class 1b). The Pipelle device has also been compared with the Explora catheter (CooperSurgical Inc; Trumbull, CT; USA) in a randomized …”
Section: Comparison Of Office-based Sampling Systemsmentioning
confidence: 99%
“…4,5 There are numerious studies in the literature comparing the effectiveness of Pipelle with D&C in patients with endometrial pathology (Table 1). These studies indicated the important role of pipelle in the diagnosis of endometrial pathology.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…On the other hand, pipelle was found to be more effective to obtain endometrial tissue for histological diagnosis compared with the Vabra aspirator with lower average cost per patient and higher procedure success rate. 4 The Pipelle Mark II sampler (Figure 3b) was designed to collect both histological and cytological samples in patients with endometrial atrophy. Studies showed that outpatient Pipelle Mark II endometrial sampling is a reliable technique in the investigation of postmenopausal bleeding and provides adequate samples for histological and cytological analysis in women with endometrial atrophy.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords: endometrial biopsy; uterine perforation; pelvic abscess; transvaginal ultrasound; magnetic resonance imaging P ipelle endometrial sampling, an outpatient, office-based procedure, provides comparative successful endometrial sampling in comparison with other techniques, which include Vabra aspirator, Novak curette, Accurette, and Explora endometrial sampling devices, and even conventional dilatation and curettage. [1][2][3][4] Pipelle has also been demonstrated as an accurate and safe device for endometrial sampling in patients with endometrial carcinoma. 5 We present an unusual occurrence in which office Pipelle endometrial sampling in a perimenopausal patient was complicated 10 days later by lower abdominal pain and intermittent fever.…”
mentioning
confidence: 98%